2012
DOI: 10.1364/boe.3.000282
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of contrast and imaging depth of ultrahigh-resolution optical coherence tomography images in 800–1700 nm wavelength region

Abstract: We investigated the wavelength dependence of imaging depth and clearness of structure in ultrahigh-resolution optical coherence tomography over a wide wavelength range. We quantitatively compared the optical properties of samples using supercontinuum sources at five wavelengths, 800 nm, 1060 nm, 1300 nm, 1550 nm, and 1700 nm, with the same system architecture. For samples of industrially used homogeneous materials with low water absorption, the attenuation coefficients of the samples were fitted using Rayleigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 26 publications
2
70
0
2
Order By: Relevance
“…There have been very few developments of long wavelength OCT beyond 1.5 μm [7][8][9][10][11][12]. We have previously demonstrated through a time-domain OCT system the significantly improved probing depth of long wavelength OCT in comparison to short wavelength sources [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There have been very few developments of long wavelength OCT beyond 1.5 μm [7][8][9][10][11][12]. We have previously demonstrated through a time-domain OCT system the significantly improved probing depth of long wavelength OCT in comparison to short wavelength sources [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, however, axial resolution decreases with increasing imaging wavelength. On a human tooth in the range 1060 nm-1700 nm, this effect clearly manifested for enamel and dentin, whereas image contrast and imaging depth were enhanced at 1700 nm [36]. It was observed that there was more variation in the wavelength dependence of total signal attenuation in enamel than in dentine.…”
Section: Optical Coherence Tomography-the Methodsmentioning
confidence: 90%
“…As well as the technical parameters of the OCT equipment, the center wavelength of the light source and the optical bandwidth are key determinants for axial resolution. For soft and hard tissues, there are characteristic dependences of wavelength of OCT signal attenuation [36]. Some authors suggested that an imaging window at 1700 nm offers an advantage over shorter wavelengths by increasing penetration depth as well as enhancing the image contrast at deeper penetration depths by reducing multiple scattering [37].…”
Section: Optical Coherence Tomography-the Methodsmentioning
confidence: 99%
“…The region of dermis was delineated on the morphological OCT image and the attenuation profile of the optical signal with depth was extracted for each region using LabVIEW software.The model for the amplitude of the signal in decibels is described in Eq. (1) [18,19].…”
Section: Oct Imagingmentioning
confidence: 99%